2007
DOI: 10.1590/s1516-35982007000500028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal stress indexes for dairy cows in tropical regions

Abstract: -Data from 359 Holstein and 54 Jersey cows (total of 1359 observations) collected in commercial herds in the northeast of Brazil were used to evaluate six environmental stress indexes. The selection criterion was the correlation between the index value with the rectal temperature (RT) and the respiratory rate (RR) of cows. Both Temperature-Humidity Index (THI) and Black Globe-Humidity Index (BGHI) had the lowest correlations with animal RT and RR. The selected indexes were the Equivalent Temperature Index (r =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
22

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 10 publications
(7 reference statements)
1
57
1
22
Order By: Relevance
“…The results demonstrated that T a was nearly as good a predictor of rectal temperatures of lactating Holsteins as any of the THI equations (R 2 =0.41 versus 0.43). Similarly, da Silva et al (2007), looking at six different indicies, found THI and BGTHI had the lowest correlations with rectal temperature and respiration rate. In Missouri, percent relative humidity is relatively low in comparison to southern United States.…”
Section: Discussionmentioning
confidence: 95%
“…The results demonstrated that T a was nearly as good a predictor of rectal temperatures of lactating Holsteins as any of the THI equations (R 2 =0.41 versus 0.43). Similarly, da Silva et al (2007), looking at six different indicies, found THI and BGTHI had the lowest correlations with rectal temperature and respiration rate. In Missouri, percent relative humidity is relatively low in comparison to southern United States.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Holstein cows bred in tropical and subtropical conditions have differences in their hair coat characteristics compared with those bred in temperate regions [6,55].…”
Section: Discussionmentioning
confidence: 99%
“…HLINew is also suggested for fat and protein content in the spring. Silva et al suggested HLI for tropical regions, and Moran and Epstein evaluated ESI for hot/dry and hot/wet climates [6,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…242, Art. 1601, Outubro, 2013 2.3.2 Efeito do manejo e de variáveis bioclimáticas sobre a taxa de gestação em vacas receptoras de embriões Nos ambientes tropicais, as elevadas temperaturas do ar, ligada à umidade e radiação alta, diminui consideravelmente a eficiência da perda de calor e, com isso, incrementa o estresse térmico (Silva et al, 2007), o que se torna limitante ao desenvolvimento, a reprodução e produção animal (Torres Júnior et al, 2008). O animal tem a capacidade de se ajustar fisiologicamente mediante estresse por calor, em função de alta umidade do ar e temperatura(o que se observa são a temperatura retal e a frequência respiratória), utilizando esses mecanismos fisiológicos o animal está tentando perder o calor absorvido (Azevedo et al, 2005;Morais et al, 2008).…”
Section: Seleção De Receptoras Aptas Ao Processo De Transferência De unclassified